Load Balancing Parallel Routing Protocol in Mobile Ad Hoc Network (International Journal of Engineering and Computer Science, 2013)
The combination of link-quality variation with the broadcasting nature of wireless channels has revealed a direction in the research of wireless networking, namely, cooperative communication. Existing system, tackle the problem of opportunistic data transfer in mobile ad hoc networks using a solution called Cooperative Opportunistic Routing in Mobile Ad hoc Networks (CORMAN). It is a pure network layer scheme which can be designed atop of wireless networking equipment. Nodes inside the network use a light-weight proactive source routing protocol to see a list of intermediate nodes that the information packets need to follow to the destination. Once associate data packet is broadcast by upstream node and goes on to be received by a downstream node any on the route and it continues it suggest that from there so will reach the destination node sooner. This can be achieved through cooperative electronic communication at the link and network layers. Since a pipeline of data transportation could promote better spatial channel reuse we enhanced our system with Load Balancing Parallel Routing Protocol (LBPRP) which distributes traffic among multiple paths) sending data in parallel form as it uses all paths in the same time. Evaluation results shows that load balancing in sending data, decreased the end-to-end delay and increased the packet delivery ratio and throughput, thus the performance of CORMAN can be improved consequently.